2015
DOI: 10.1007/s11356-015-4563-y
|View full text |Cite
|
Sign up to set email alerts
|

Detoxification strategies and regulation of oxygen production and flowering of Platanus acerifolia under lead (Pb) stress by transcriptome analysis

Abstract: Toxic metal pollution is a major environmental problem that has received wide attention. Platanus acerifolia (London plane tree) is an important greening tree species that can adapt to environmental pollution. The genetic basis and molecular mechanisms associated with the ability of P. acerifolia to respond lead (Pb) stress have not been reported so far. In this study, 16,246 unigenes differentially expressed unigenes that were obtained from P. acerifolia under Pb stress using next-generation sequencing. Essen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 73 publications
1
16
0
Order By: Relevance
“…The GO term and KEGG enrichment analyses showed that terms for transport (GO:0006810) and membrane (GO:0016020, GO:0031224) (S3 Table), and pathways related to signal (ko03320, ko04075) and energy metabolism (ko00040, ko00020, ko00196, ko00010) (Table 3), were significantly enriched in the identified DEGs. These results were in agreement with previous studies that reported that heavy metals damaged plant membrane systems, inhibited photosynthesis, and delayed plant growth [27, 3840]. …”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…The GO term and KEGG enrichment analyses showed that terms for transport (GO:0006810) and membrane (GO:0016020, GO:0031224) (S3 Table), and pathways related to signal (ko03320, ko04075) and energy metabolism (ko00040, ko00020, ko00196, ko00010) (Table 3), were significantly enriched in the identified DEGs. These results were in agreement with previous studies that reported that heavy metals damaged plant membrane systems, inhibited photosynthesis, and delayed plant growth [27, 3840]. …”
Section: Discussionsupporting
confidence: 94%
“…Previous studies have shown that photosynthesis is sensitive to heavy metal stress [27]. In this study, the KEGG pathways for “photosynthesis—antenna proteins” (ko00196) were significantly enriched in Pb-stress cDNA libraries (Table 3), in which the expression levels of 10 DEGs coding for chlorophyll a/b-binding protein (light-harvesting complex I protein) were significantly upregulated (S5 Table).…”
Section: Resultsmentioning
confidence: 73%
See 3 more Smart Citations